Knowing What We Don't Know: A Survey of School Nurse Information Needs. - Nickum, Annie "Nicky"; Hanneke, Rosie; Shannon, Robin (Journal of School Nursing, 2025)
Providing complex care for students requires an informed school nurse workforce. However, school nurses, many of whom work independently, may not know where to find necessary information. This study seeks to understand the information needs of school nurses by conducting a needs assessment survey within the state of Illinois. A survey was disseminated through three statewide professional listservs to determine the types of care-related questions school nurses ask as part of their regular duties and which resources they use to answer those questions. School nurses' information needs vary widely, and they rely on numerous sources to answer clinical questions. They are responsible for the well-being of hundreds to thousands of children. While they are comfortable searching for information, they are motivated to further develop research skills.